Manganese transport into the brain - Aschner, Michael (2015)
An important process in the toxicologic outcome of exposure to metals is their transport from plasma into the brain across the capillary endothelial cells that comprise the blood-brain barrier (BBB). The review, briefly delineates the known transport mechanisms of manganese (Mn) across the BBB, a crucial step in Mn accumulation in the brain. Herein, we discuss the distribution of Mn in the central nervous system (CNS) and identify putative transport mechanism for Mn, emphasize the close chemical interaction between Mn and iron (Fe) and the role of transferrin (Tf) and divalent metal transport1 (DMT1) in this process.